L’Antropocene architettonico. Sulla formazione di mondo - Barison, Marcello (Aesthetica Preprint, 2020)
One of the most significant cross-disciplinary research fields which recently underwent a major development is the study of the Anthropocene. Intersecting the Anthropocene discourse with the current research in philosophy of architecture, I detected two major lacks in the state of the art: 1. Even if architecture is indisputably one of the main factors modifying the surface structure of the Earth, the discourse of the Anthropocene did not elaborate any satisfactory conceptual paradigm to interpret its role. 2. Although in recent years philosophy of architecture has undergone a notable development, there still is no clear general definition of its scope and objectives: the discipline completely lacks a systematic foundation. My paper’s approach will consist in addressing 2 with 1 and 1 with 2, i.e., in turning each of these lacks into a powerful strategical tool to tackle and overcome the deficiency of the other: I address 1 with 2: a philosophical understanding of architecture, based on an extension of the concept of world-formation, allows to systematically conceive the architecture of the Anthropocene. I address 2 with 1: questioning the architecture of the Anthropocene allows the philosophy of architecture to ground its entire disciplinary field on the unitary concept of world-formation.